Analisis dampak ekonomi obyek wisata terhadap pendapatan masyarakat lokal studi kasus Taman Nasional Bukit Tiga Puluh (TNBT) Kabupaten Indragiri Hulu - Raja Andrea Malantino; Eriyati '; Nobel Aqualdo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research was conducted in Indragiri Hulu. The purpose of this studywas to determine the economic impact of tourism on local people's income Case Study Thirty Hill National Park (BTNP) Indragiri Hulu.Types and sources of data used in this study is primary data in the capture as many as 100 respondents and secondary data obtained from the agencies or parties related to this research. The analytical method used in this research is descriptive quantitative method.Based on the research results, the conclusion of this study is the attractionThirty Hill National Park as a tourist a positive impact on the economy of the surrounding community. It can be seen from the increase in people's income, increased employment and improved infrastructure. Visible public monthly expenditure increased as the Thirty Hill National Park.Keywords : Economic Impact, Income